1979
DOI: 10.1017/s0033291700032098
|View full text |Cite
|
Sign up to set email alerts
|

The effect of sex, marriage and age at first admission on the hospitalization of schizophrenics during 2 years followings discharge

Abstract: SYNOPSIS Two hundred and eighty-two schizophrenics discharged from St John's Hospital, Stone, were followed-up. The reliability of the diagnosis was measured by the extent of agreement among the hospital clinicians. The number of readmissions and the time spent in hospital were ascertained and correlated with the sex, civil state and age at first admission of the subjects.It was found that a higher proportion of males than of females was readmitted; that the proportion of single persons among male schizophreni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…The largest number of admissions (77 % Clare, 68 % Wexford) were single individuals, predominantly male 52 % Clare and 44 % Wexford). The low number ofadmittants who were married (18% Clare and 24 % Its consistent with the research suggesting marital status may have a buffering effect on psychiatric hospitalisation (Tischler et al 1975;Watt & Szulecka, 1979). Both counties had a low number of first admittants who were widows (5 % Clare and 6 % Wexford).…”
Section: First Admissionssupporting
confidence: 81%
“…The largest number of admissions (77 % Clare, 68 % Wexford) were single individuals, predominantly male 52 % Clare and 44 % Wexford). The low number ofadmittants who were married (18% Clare and 24 % Its consistent with the research suggesting marital status may have a buffering effect on psychiatric hospitalisation (Tischler et al 1975;Watt & Szulecka, 1979). Both counties had a low number of first admittants who were widows (5 % Clare and 6 % Wexford).…”
Section: First Admissionssupporting
confidence: 81%
“…The earlier age of onset in males has been repeatedly reported in large-scale studies of schizophrenics (Malzberg, 1935;Landis & Page, 1938;Rennie, 1941;Shepherd, 1957;Rosenthal, 1961;Brown et al 1966;Kay, 1972;Forrest & Hay, 1972;Nystrup, 1976;Watt & Szulecka, 1979;Lewine, 1981;Loranger, 1984;Sartorius et al, 1986). Lewine (1980), in a study of 97 cases, found that this could not be accounted an artefact as a result of a difference in the interval between the onset of symptoms and admissions to hospital, nor by diagnostic discrepancies since it was present when both broad and narrow criteria are employed .…”
Section: Outcome and Sociodemographic Factorsmentioning
confidence: 67%
“…Shepherd (1957) reported that more schizophrenic males are unmarried than in any other diagnostic category. Single schizophrenic men are more often readmitted than single women, a difference which does not occur between married male and female schizophrenics (Watt & Szulecka, 1979).…”
Section: Outcome and Sociodemographic Factorsmentioning
confidence: 94%
See 1 more Smart Citation
“…• Initial symptoms in both diseases commonly manifest between the second and third decade of life [27,28].…”
Section: Epidemiologic Data On the Association Between Toxoplasmosis mentioning
confidence: 99%